Nickel-Catalyzed Asymmetric Domino Ring Opening/Cross-Coupling Reaction of Cyclobutanones via a Reductive Strategy - Ding, Decai; Dong, Haiyan; Wang, Chuan (iScience, 2020)
Herein we demonstrate the successful application of reductive strategy in the asymmetric domino ring opening/cross-coupling reaction of prochiral cyclobutanones. Under the catalysis of a chiral nickel complex, various aryl iodide-tethered cyclobutanones were reacted with alkyl bromides as the electrophilic coupling partner, providing a variety of chiral indanones bearing a quaternary stereogenic center in highly enantioselective manner, which can be further converted to diverse benzene-fused cyclic compounds including indane, indene, dihydrocoumarin, and dihydroquinolinone. The preliminary mechanistic investigations support a mechanism involving Ni(I)-mediated enantiotopic C−C σ-bond activation of cyclobutanones as key elementary step in the catalytic cycle. [Display omitted] •Asymmetric ring opening of prochiralcyclobutanones via reductive Nickel-catalysis•Merger of electrophilic ring opening and cross-electrophile coupling•Chiral indanones were synthesized in highly enantioselective manner Catalysis; Organic Synthesis; Organic Reaction